Titanium Dioxide Nanofibers and Microparticles Containing Nickel Nanoparticles. (19th November 2012) - Sheikh, Faheem A.; Macossay, Javier; Kanjwal, Muzafar A.; Abdal-hay, Abdalla; Tantry, Mudasir A.; Kim, Hern
Abstract : The present study reports on the introduction of various nanocatalysts containing nickel (Ni) nanoparticles (NPs) embedded within TiO2 nanofibers and TiO2 microparticles. Typically, a sol-gel consisting of titanium isopropoxide and Ni NPs was prepared to produce TiO2 nanofibers by the electrospinning process. Similarly, TiO2 microparticles containing Ni were prepared using a sol-gel syntheses process. The resultant structures were studied by SEM analyses, which confirmed well-obtained nanofibers and microparticles. Further, the XRD results demonstrated the crystalline feature of both TiO2 and Ni in the obtained composites. Internal morphology of prepared nanofibers and microparticles containing Ni NPs was characterized by TEM, which demonstrated characteristic structures with good dispersion of Ni NPs. In addition, the prepared structures were studied as a model for hydrogen production applications. The catalytic activity of the prepared materials was studied by in situ hydrolysis of NaBH4, which indicated that the nanofibers containing Ni NPs can lead to produce higher amounts of hydrogen when compared to other microparticles, also reported in this paper. Overall, these results confirm the potential use of these materials in hydrogen production systems.